What is the Impact of Feedback as a Central Part of Formative Assessment on Physiotherapy Students Who Have Multiple Educators? - Morris, Jane; Stew, Graham (International Journal of Practice-based Learning in Health and Social Care, 2016)
The purpose of this study was to gain insight into physiotherapy students experience of feedback as an integral part of formative assessment on placements. A purposive sample of nine physiotherapy students from a pre-registration problem-based learning programme and four physiotherapy practice-based educators was selected. An interpretative phenomenological approach was adopted using in depth semi-structured interviews. Reflective logs and theme boards (memory collages) were used to promote student participants reflection prior to interview. Five main themes emerged from the data: feeling overloaded, challenges of multiple educators, problem-based learning influences, fulfilling experiences, learning through relationships. This paper will focus on two of the main themes: * challenges of multiple physiotherapy educators, * learning through relationships. Lack of communication between educators in a multiple physiotherapy educator model resulted in conflicting feedback that was challenging for students on placement. However, participants valued feedback from other health professionals. Potential exists for more effective use of interprofessional team members to provide feedback as part of ongoing formative assessment. In a changing practice environment where practice educators inevitably face increasing time constraints, use of other team members and peers to provide student feedback should be promoted to facilitate interprofessional ways of working.